Chronic Apraxia of Speech and “Broca’s Area” - Trupe, Lydia A. (2013)
BACKGROUND AND PURPOSE: Apraxia of speech (AOS) is an impairment of motor planning and programming of speech articulation, and is often considered an important stroke syndrome, localizable to Broca’s area. However, an influential study shed doubt on this localization, and reported that AOS is attributable to lesions of the anterior insula, based on an association between chronic AOS and anterior insula lesions. We hypothesized that chronic AOS is associated with large lesions (which include the insula) or lesions to Broca’s area. METHOD: We tested 34 participants with chronic left supratentorial stroke on an AOS battery and obtained concurrent MRI. We evaluated associations between AOS and locations and volume of infarct. RESULTS: The presence of chronic AOS (n=17) was associated with volume of infarct, but was also associated with infarct in Broca’s area (and several other regions, but not anterior insula) in both volume-adjusted and age-adjusted linear regression and the dichotomous analysis. Carotid dissection was more common, and cardioembolism less common, as a cause of stroke in patients with AOS compared those without. Severity of AOS was also strongly associated with lesion volume. CONCLUSIONS: Persistence of AOS after twelve months is associated with large left hemispheric stroke and strokes that involve Broca’s area or other relatively anterior areas to which it is structurally and/or functionally connected. Patients with such lesions may benefit from early training in the use of technologies to support speech production and communication.